Assessment of Disulfide-linked Gold Nanoparticles as Colorimetric Sensor for Human Chorionic Gonadotropin Detection - Mohd Yusri, M. A. Y.; Abu Hassan, M. H.; Azhari, S. (Universiti Sains Islam Malaysia, 2024)
Gold nanoparticles (AuNPs) are a highly versatile compound to be used in sensing components due to their unique physicochemical and optical properties. Due to its flexibility for surface conjugation, glutathione disulfide-linked gold nanoparticle (AuNP-GSSG) was produced in this study to assess its sensing performance as a colorimetric sensor for human chorionic gonadotropin (HCG). Spectroscopic characterization of AuNP-GSSG confirmed the conjugation of GSSG onto the surfaceofAuNPs.AuNP-GSSGalsoshowedhighsensoryperformancewithgoodlinearityandlowdetectionlimit.However,due to the high percentage of interference, usage of AuNP-GSSG as an HCG sensor requires further pre-treatment step to reduce the interference and increase the sensor accuracy.